PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD T OHETGER (NHT) BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJARAN IPAS KELAS IV SDN CIKANDE PERMAI - Pipit Apitasari; Umalihayati; Syarifah Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the implementation of the Numbered Head Together (NHT) Model assisted by Wordwall media on the learning outcomes of Natural and Social Sciences (IPAS) in fourth-grade students of SDN Cikande Permai. This study uses quantitative research with a pre-experimental approach. This study uses the one group pretest-posttest. Data collection techniques are tests to determine learning outcomes, as well as student response questionnaires to the application of Wordwall media. Data analysis techniques used in this study are descriptive data analysis and inferential data analysis. This study shows the results of data analysis, the average pretest experiment was 45.8 and posttest experiment 83.3. The results of the study showed that there was a significant difference between the pretest and posttest. This indicates that there is an increase in student learning outcomes using the Numbered Head Together (NHT) model assisted by Wordwall compared to students who use conventional methods. The results of student response questionnaire data processing produced an average value of 84.56. The data analysis resultsabove demonstrate the influence of the Numbered Heads Together (NHT) learning model with the aid of wordwalls on student learning outcomes, as evidenced by the increase in post-test scores.